Dalit theology, boundary crossings and liberation in India : A biblical and postcolonial study - Skaria, Jobymon (London : Bloomsbury, 2024)
Jobymon Skaria, an Indian St Thomas Christian Scholar, offers a critique of Indian Christian theology and suggests that constructive dialogues between Biblical and dissenting Dalit voices - such as Chokhamela, Karmamela, Ravidas, Kabir, Nandanar and Narayana Guru - could set right the imbalance within Dalit theology, and could establish dialogical partnerships between Dalit Theologians, non-Dalit Christians and Syrian Christians. Drawing on Biblical and socio-historical resources, this book examines a radical, yet overlooked aspect of Dalit cultural and religious history which would empower the Dalits in their everyday existences
Keywords: Christianity -- India; Dalits -- Religion -- India; Liberation theology -- India